Chronobiological peculiarities of psychic disorders course at the example of metabolic syndrome patients - Abdriachimova, Ts. B.; Kleban, K. I.; Sapon, D. P. (Journal of Education, Health and Sport, 2017)
Desynchronosis presenting in patients with metabolic syndrome significantly affects the underlying metabolism, eating behavior, mental and physical activity. On on example of a clinical case, patients with a depressive episode of moderate severity and clinically confirmed metabolic syndrome on the treatment achieved a significant improvement on their mental status and reduced manifestations on metabolic disorders. The study on chronobiological features on the course on mental disorders on combination with metabolic syndrome is a promising direction on medical practice, which will improve the results on treatment on patients with a similar pathology.